1958
DOI: 10.2118/968-g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flow Rate on Paraffin Accumulation in Plastic, Steel, and Coated Pipe

Abstract: Published in Petroleum Transactions, AIME, Volume 213, 1958, pages 80–84. Introduction The accumulation of paraffin deposits in tubular goods has been recognized as a major production problem since the inception of the petroleum industry. This problem is not limited to any particular geographical area nor is it limited to a specific type of crude oil. Generally speaking, "paraffin" deposition pertains to the deposition of any predominantly organic material in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…Therefore, in a large number of experiments, the inner walls of pipes were coated with low surface energy polymer composite coatings, and their properties to inhibit paraffin deposition were investigated by controlling the free energy of the substrate surface (Dotto and Camargo 2010). Jessen and Howell (1958) studied the paraffin deposition on the surface of different pipe materials (Jessen and Howell 1958). It was found that the paraffin deposition on the surface of smooth plastic was much smaller than that on a steel surface and maintained a low paraffin deposition for a long time.…”
Section: Low Surface Energy Coatingsmentioning
confidence: 99%
“…Therefore, in a large number of experiments, the inner walls of pipes were coated with low surface energy polymer composite coatings, and their properties to inhibit paraffin deposition were investigated by controlling the free energy of the substrate surface (Dotto and Camargo 2010). Jessen and Howell (1958) studied the paraffin deposition on the surface of different pipe materials (Jessen and Howell 1958). It was found that the paraffin deposition on the surface of smooth plastic was much smaller than that on a steel surface and maintained a low paraffin deposition for a long time.…”
Section: Low Surface Energy Coatingsmentioning
confidence: 99%
“…Many of the authors listed in the bibliography have studied the deposition of paraffin; this section will summarize their observations. For more detailed information, the reader is referred t", : Agrawal et al (1989), Agrawal et al (1990), Brown (1940), Bucaram (1967), Burger et al (1981), Charles (1984), Cole and Jessen (1960), Gdanski (1984), Howell and Jessen (1956), Hunt (1962), Jessen and Howell (1958), Jorda (1966), Matloch and Newberry(1983), Mills (1932), , Newberry and Barker (1985), Patton (1970), Price (1971), Reistle (1928), Reistle and Blade (1932), Shock et al (1955), Sutton andRoberts (1974), Thomas (1988), Uren (1953), Weingarten and Euchner (1988), Won (1986), and Wright (1951 Other less widely used tests for the examination of wax are: (1) a visual study to determine the color and particulate adherence qualities;…”
Section: Deposition Of Paraffinsmentioning
confidence: 99%
“…Other things being equal, the rate of deposit was governed by surface roughness alone. Jessen (1958) carded out a series of deposition experiments, the conclusions of which were as follows: (1) the rate of deposition in a steel pipe varied with flow rate, reaching a maximum just prior to change from viscous to turbulent flow. (2) deposition of paraffin on various kinds of plastic pipe showed the same general dependence on flow rate as for steel pipe; however, the amount accumulaP._xiwas appreciably less on plastic than on steel pipe, 3when cooling of the oil from temperatures above the cloud point took place at the pipe wall, an increased deposit of paraffin resulted when compared with that obtained when the oil had been cooled below the cloud point prior to circulation through the pipe, (4) the rate of accum_alation of paraffin on plastic pipe seemed to increase with the degree of wettability by the crude oil, (5) plastic pipe did not entirely eliminate the problem, but the rate of deposition on plastic or plastic lined pipe was substantially lower than on steel or aluminum pipe and (6) predictions as to the severity of the paraffin problem must be based not only on cloud point but also on concentration of wax in _lution.…”
Section: Studiesmentioning
confidence: 99%
“…The influencing factors of wax deposition include crude oil composition, transportation temperature, temperature difference between oil and pipe wall, flow velocity, flow pattern, material of pipe, deposition time, and so on. Consequently, scholars have researched the problem of wax deposition for a long time; however, the mechanism of wax deposition is still not recognized thoroughly . The concept of ‘aging’ is a good supplement to the traditional wax deposition mechanism .…”
Section: Introductionmentioning
confidence: 99%